2021
DOI: 10.1101/2021.04.27.441655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A broadly neutralizing antibody protects against SARS-CoV, pre-emergent bat CoVs, and SARS-CoV-2 variants in mice

Abstract: SARS-CoV in 2003, SARS-CoV-2 in 2019, and SARS-CoV-2 variants of concern (VOC) can cause deadly infections, underlining the importance of developing broadly effective countermeasures against Group 2B Sarbecoviruses, which could be key in the rapid prevention and mitigation of future zoonotic events. Here, we demonstrate the neutralization of SARS-CoV, bat CoVs WIV-1 and RsSHC014, and SARS-CoV-2 variants D614G, B.1.1.7, B.1.429, B1.351 by a receptor-binding domain (RBD)-specific antibody DH1047. Prophylactic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…We demonstrate here that S309, the parent mAb of sotrovimab which has received an emergency use authorization from the FDA, is unaffected by antigenic drift observed in variants of concern and interest due to recognition of a conserved RBD epitope (12,15,56). The recent discovery of multiple additional conserved antigenic sites recognized by RBD-specific mAbs with (near) pan-sarbecovirus neutralizing activity (16,17,21,(73)(74)(75) and the anticipated continued emergence of SARS-CoV-2 variants motivate the clinical development and deployment of some of these mAbs for prophylaxis with at-risk patients and for treatments of unvaccinated individuals or breakthrough infections. Moreover, next-generation vaccine candidates have recently been described to elicit broad sarbecovirus immunity (41,76,77), holding the promise to be resilient to the emergence of SARS-CoV-2 variants and of new zoonotic sarbecoviruses.…”
Section: And Biolayer Interferometry (Fig 2i Fig S4x Tablementioning
confidence: 99%
“…We demonstrate here that S309, the parent mAb of sotrovimab which has received an emergency use authorization from the FDA, is unaffected by antigenic drift observed in variants of concern and interest due to recognition of a conserved RBD epitope (12,15,56). The recent discovery of multiple additional conserved antigenic sites recognized by RBD-specific mAbs with (near) pan-sarbecovirus neutralizing activity (16,17,21,(73)(74)(75) and the anticipated continued emergence of SARS-CoV-2 variants motivate the clinical development and deployment of some of these mAbs for prophylaxis with at-risk patients and for treatments of unvaccinated individuals or breakthrough infections. Moreover, next-generation vaccine candidates have recently been described to elicit broad sarbecovirus immunity (41,76,77), holding the promise to be resilient to the emergence of SARS-CoV-2 variants and of new zoonotic sarbecoviruses.…”
Section: And Biolayer Interferometry (Fig 2i Fig S4x Tablementioning
confidence: 99%
“…Furthermore, preclinical studies have shown similar reductions in heterologous neutralizing titers against SARS-CoV-2 variants of concern, such as B.1.351, for RBD nanoparticle immunogens and S-based immunogens (37,50). Finally, RBD antigens can be leveraged to elicit neutralizing responses against the sarbecovirus subgenus through multivalent display on nanoparticles (36,50) and have recently been shown to be targeted by broadly neutralizing monoclonal antibodies (42,(51)(52)(53)(54)(55)(56). In summary, the potential for improved scalability and stability of RBD-based immunogens compared to S-based immunogens, while maintaining similar immunogenicity, affirms the RBD as a bona fide antigen for use in protein-based vaccines.…”
Section: Introductionmentioning
confidence: 98%
“…(C) Emergent pathogens are numerous and diverse but the probability of establishment is small owing to narrow requirements for host and pathogen factors that are compatible with persistent transmission. (D) Opportunities for viral emergence depend on previously established pathogens that block or partially block immune niches or gaps via cross-reactive immune responses (e.g., for coronaviruses [84]).…”
Section: Hypothesis 2: Nonlinear Rates Of Coronavirus Spillover In Human Historymentioning
confidence: 99%
“…Immunity against coronaviruses is suggested to be relatively short (e.g., reinfection has been often observed at 12 months for endemic human coronaviruses from multi-decade longitudinal studies) [80][81][82]. In addition, immunity against endemic coronaviruses can be cross-reactive, and (based on analyzing the time-series for cases of coexisting species [59], in conjunction with systems serology approaches identifying convalescent plasma viral neutralization capacity [83]) can be to some extent cross-protective [2,84]. If the immune response elicited by each virus reduces viral growth more than it does for other competing viruses, then coexistence may ensueassuming similar R 0 magnitudes.…”
Section: Hypothesis 5: Host Immunological Niche and Limits To Establishmentmentioning
confidence: 99%